The Role of MicroRNAs in Regulatory T Cells - Chao Liu; Nannan Li; Guijian Liu (Journal of Immunology Research)
MicroRNAs are a class of conserved, 20 nt-23 nt long, noncoding small RNAs that inhibit expression of their respective target genes in different cell types. Regulatory T cells (Tregs) are a subpopulation of T cells that negatively regulate immune responses, which is essential to immune homeostasis. Recent studies have indicated that microRNAs play an important role in the proliferation, differentiation, and functions of Treg. Here, we review the recent progress in understanding the roles of microRNAs in Treg and their dysregulation in immune-related diseases. This ongoing research continues to expand the understanding of Treg regulation and the mechanisms of immune disorders.